Designing compound exercises with hardware technology and its impact on some physical and skill abilities of the Airways Club players under (19) years old - Jasim, Abbas; Abbas, Elaf (Journal of Physical Education, 2023)
The aim of the research is to design compound exercises with hardware technology to find out the extent of their impact on some of the physical and skillful abilities of soccer players. And to identify the effect of compound exercises designed on some physical abilities. And also to identify The effect of complex exercises designed on some of the skill abilities of soccer players. A test of the equivalence of the research sample was carried out with the torsion coefficient, and it was found that its value ranged between (±1). The tests were implemented within two days, and accordingly, the duration of the main research experiment was (8) weeks, three training units per week.